Notes on the Hungarian Translation of Margaret Cavendish’s The Description of a New World, Called the Blazing-World (1666) - Barta, Alexandra (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The paper offers insight into some of the challenges of translating Margaret Cavendish’s The Blazing World (1666) into Hungarian. Although Cavendish appears in some comprehensive literary histories and magazine articles published in Hungary, her works have never been translated into the language. The current paper is based on the ongoing translation of Cavendish’s widely studied utopian romance. The paper opens with a brief glimpse at the intellectual context of the author and her peculiar position in the male-dominated world of the Scientific Revolution. This is followed by a discussion of questions encountered during the translation of the first, "romancical" part of the text, with special focus on its unique use of Northern geography. While examining the geographical context of the utopia, the paper also explores the potential influence of contemporary maps on the imaginary geography described by Cavendish, together with the maritime lexicon characteristic of this section of the text.